Способ пожаротушения в помещениях и устройство для его осуществления - Барсуков В. Д. Виталий Дементьевич; Басалаев С. А. Сергей Александрович; Голдаев С. В. Сергей Васильевич; Минькова Н. П. Наталья Петровна
опубл. 20.10.09